Inspection of real and imputed genotypes reveled 76 SNPs associated to rear udder height in Holstein cattle - Gonzalez, Mirvana; Villa, Rafael; Villa, Carlos; Gonzalez, Victor; Montano, Martin; Medina, Gerardo; Mahadevan, Pad (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This paper presents the obtained result of a study that realizes to associate a set of real and imputed single nucleotide polymorphisms (SNP) genotypes to the rear udder height in Holstein cows. Materials and methods: Forty-six Holstein cows from an arid zone of Mexico were phenotyped and genotyped for this study. Blood samples were used for DNA extraction, genotyping was performed with the Illumina BovineLD Bead chip which interrogates 6,912 SNPs genome-wide, and imputation was performed using the Findhap software. After QC filters, a total of 22,251 high quality and informative SNPs were inspected. Results: The results showed the detection of 76 significant SNPs throughout the complete genome. Significant SNPs fall inside 111 Quantitative Loci Traits related to protein percentage, milk yield, and fat, among others, in chromosomes 1, 2, 3, 5, 6, 9, 10, 11, 12, 13, 19, 20, 21, 23, 26, 27, and 29. Similarly, results confirm that a genotype imputation is a convenient option for genome-wide covering when selecting economic traits with low-density real SNP panels. Conclusion: This study contributes to establishing a low-cost and profitable strategy for applying genomic selection in developing countries. Adv. Vet. Anim. Res., 7(2): 234-241, June 2020